“Creating Cool Stuff”: Pupils’ Experience of the BBC micro:bit - Sentance, Sue; Waite, Jane; Hodges, Steve; MacLeod, Emily; Yeomans, Lucy (Proceedings of the 2017 ACM SIGCSE Technical Symposium on Computer Science Education, 2017)
The recent introduction of computer science (CS) education into schools in many countries has led to a surge in interest in programming tools and approaches which make CS concepts and tasks engaging, motivating and accessible to all. There is renewed interest in supporting learning through physical computing, which has been shown to be motivational whilst offering opportunities for collaboration and creativity. Within this context the BBC recently led a collaborative venture in the UK to develop a portable and low-cost programmable device. The consortium funded and produced one million devices, enough for every 11-12 year-old in the UK. In this paper, we report on what we believe to be the first study to investigate the usability and affordances of the BBC micro:bit. We interviewed 15 teachers and 54 pupils in schools in England about their experiences with the device who were, in general, enthusiastic about the potential of the BBC micro:bit. We describe pupils' experiences in terms of usability, creativity, the tangibility of the device and their learning of programming, and analyse their experiences in the context of previously reported benefits of physical computing.